Epithelial cells with high TOP2A expression promote cervical cancer progression by regulating the transcription factor FOXM1 - Sun, Wei; Chen, Lu; Feng, Xiaoling (Frontiers in Oncology, 2025)
BackgroundCervical cancer (CC) remains a major malignancy threatening women’s health, with high-grade squamous intraepithelial lesions playing a critical role in the progression toward CC. Exploring the molecular characteristics of epithelial cells (EPCs) as high-stage intraepithelial neoplasia evolves into CC is essential for the development of effective targeted drugs for cervical cancer. Single-cell RNA sequencing technology can fully understand the immune response at each molecular level, providing new ideas and directions for the precise treatment of CC.MethodsSingle-cell RNA sequencing was employed to comprehensively map EPCs characteristics. The differentiation trajectory of EPCs was inferred using Slingshot, while enrichment analysis highlighted the biological functions of EPCs. Cellchat visualized cell-cell interactions, and SCENIC was used to infer transcription factor regulatory networks in EPCs. CCK-8, colony formation, and EDU experiments were used to verify cell proliferation changes. Scratch assays and transwell assays were used to verify cell migration and invasion.ResultsA distinct EPCs subpopulation with high TOP2A expression was identified, predominantly originating from tumor tissues. This subpopulation exhibited disrupted mitosis and cell cycle regulation, along with features of high proliferation, high energy metabolism, and matrix plasticity. It played a key role in shaping the tumor microenvironment via the LAMC1-(ITGA3-ITGB1) signaling pathway. FOXM1, a key transcription factor in this cell subpopulation, significantly inhibited the proliferation and invasion of cervical cancer cells.ConclusionThrough in-depth analysis of EPCs, this study provides promising insights and potential therapeutic targets for precision targeted treatment strategies for CC.